Trichome composition of leaf domatia as potential morphoanatomical marker of the four commercially viable Coffea species [Review note] - Balinado, Lloyd O.; Cardenas, Lourdes B. (2019)
Trichomes are epidermal extensions that play a role in providing structural defense, affecting photosynthesis, and accumulating secondary metabolites. These trichomes may also occur in leaf domatia ? providing various roles for interaction with mites and other arthropods. In the present study, leaf domatia of four Coffea species ? namely C. arabica L., C. canephora Pierre ex. A. Froehner, C. liberica Hiern, and C. excelsa A. Chev ? were examined for trichome composition. Leaf domatia were observed in all species and were found to be in association with trichomes. Its distribution, on the other hand, interestingly differed among species and could thus serve as a potential morphoanatomical marker. Trichomes in C. arabica were observed to exist around domatia pore, while it forms along the adjacent epidermal tissue in C. canephora. However, no difference was found between C. liberica and C. excelsa. Both exhibited trichome formation within domatia chambers and along the entry point of domatia pore. (Author's abstract)